Learning Management of Physical Education for Sports and Health During the Covid-19 Pandemic in MIN 2 Palangka Raya City - abdurrahman abdurrahman; Ahmadi Ahmadi; Aulia Mustika Ilmiani; Faridatul Hasanah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Jember, 2022)
This study aims to determine the process of implementing PJOK learning in limited face-to-face learning during the Covid-19 pandemic in class V MIN 2 Palangka Raya City. This type of research is qualitative with case studies. Data collection techniques by observation and interviews. Meanwhile, data analysis uses descriptive data analysis. The results of this study show that:1) planning for sports and health physical education learning during the Covid-19 pandemic in MIN 2 Palangka Raya City: Teachers plan the PJOK class V learning program, develop the Annual Program, carry out Semester Program activities, carry out learning plans in the learning syllabus, distribute effective weeks.2) Implementation of Sports and Health Physical Education learning in MIN 2 Palangka Raya City, namely: development of the Annual Program into the Learning Implementation Plan, carrying out Semester Program activities, implementation of learning plans in the learning syllabus, online teaching, and learning process activities teachers explain teaching materials, apply learning methods. Penelitian ini bertujuan untuk mengetahui proses pelaksanaan pembelajaran PJOK pada PTM terbatas pada masa pandemi covid-19 di kelas V MIN 2 Kota Palangka Raya. Jenis penelitian ini yaitu kualitatif dengan studi kasus. Tehnik pengumpulan data dengan observasi dan wawancara. Sedangkan analisis data menggunakan analisis data deskriptif. Hasil penelitian ini menungjukkan, bahwa: 1) perencanaan pembelajaran pendidikan jasmani olahraga dan kesehatan masa pandemi Covid-19 Di MIN 2 Kota Palangka Raya: Guru merencanakan program pembelajaran PJOK kelas V, pengembangan Program Tahunan, melaksanakan kegiatan-kegiatan Program Semester, melaksanakan rencana pembelajaran dalam silabus pembelajaran, pendistrisbusian minggu efektif. 2) Pelaksanaan pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan di MIN 2 Kota Palangka Raya, yaitu: pengembangan Program Tahunan ke dalam Rencana Pelaksanaan Pembelajaran, melaksanakan kegiatan-kegiatan Program Semester, melaksanakan rencana pembelajaran dalam silabus pembelajaran, dalam kegiatan proses belajar mengajar secara daring guru menjelaskan materi ajar, menerapkan metode pembelajaran.